2023
DOI: 10.3233/jad-220640
|View full text |Cite
|
Sign up to set email alerts
|

HMGCS2-Induced Autophagic Degradation of Tau Involves Ketone Body and ANKRD24

Abstract: Background: Accumulation of hyperphosphorylated Tau (pTau) contributes to the formation of neurofibrillary tangles in Alzheimer’s disease (AD), and targeting Tau/pTau metabolism has emerged as a therapeutic approach. We have previously reported that mitochondrial 3-hydroxy-3-methylglutaryl-COA synthase 2 (HMGCS2) is involved in AD by promoting autophagic clearance of amyloid-β protein precursor via ketone body-associated mechanism, whether HMGCS2 may also regulate Tau metabolism remains elusive. Objective: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The hippocampus and prefrontal cortex respond differentially to changes in autophagy markers and levels of KB utilization upon KD administration, suggesting a potential interconnection between KB metabolism and autophagy [ 187 ]. Moreover, the ketogenic enzyme, HMGCS2, promotes the autophagic clearance of APP and tau/phosphorylated tau, mimicked by KB consumption during AD pathophysiology [ 188 , 189 ]. These observations indicate that HMGCS2-induced KB production plays a crucial role in autophagy regulation.…”
Section: Molecular Mechanisms Of the Neuroprotective Effects Of Kbs A...mentioning
confidence: 99%
“…The hippocampus and prefrontal cortex respond differentially to changes in autophagy markers and levels of KB utilization upon KD administration, suggesting a potential interconnection between KB metabolism and autophagy [ 187 ]. Moreover, the ketogenic enzyme, HMGCS2, promotes the autophagic clearance of APP and tau/phosphorylated tau, mimicked by KB consumption during AD pathophysiology [ 188 , 189 ]. These observations indicate that HMGCS2-induced KB production plays a crucial role in autophagy regulation.…”
Section: Molecular Mechanisms Of the Neuroprotective Effects Of Kbs A...mentioning
confidence: 99%
“…More recently, the same group reported that HMGCS2 also regulates Tau and pTau degradation through autophagy in astrocytoma and neuroblastoma cell lines. The authors show that this effect is mediated by KBs, which promote autophagy ( Hu et al, 2023 ). Overall, these findings support that the beneficial effects of ketogenesis in AD rodent models might be related to the stimulation of autophagy and the degradation of pathologic aggregates of amyloid-β and Tau.…”
Section: Ketone Bodies and Disrupted Proteostasis In Alzheimer's And ...mentioning
confidence: 99%
“…Reduction of total plaque burden in the brain of mouse models of AD has also been replicated in other ketosis-inducing dietary interventions, such as calorie restriction and intermittent fasting 44,45 . Multiple recent studies have implicated the role of ketone bodies in regulating autophagic flux and chaperone-mediated autophagy, including clearance of amyloid-b and pathogenic tau [46][47][48][49][50] . However, a clear mechanism by which bHB directly interacts with proteins or protein clearance machineries has not been identified.…”
mentioning
confidence: 99%